Increased Ectomycorrhizal Fungal Abundance after Long-Term Fertilization and Warming of Two Arctic Tundra Ecosystems - Clemmensen, Karina E.; Michelsen, Anders; Jonasson, Sven; Shaver, Gaius R. (The New phytologist, 2006)
$\bullet$ Shrub abundance is expected to increase with enhanced temperature and nutrient availability in the Arctic, and associated changes in abundance of ectomycorrhizal (EM) fungi could be a key link between plant responses and longer-term changes in soil organic matter storage. This study quantifies the response in EM fungal abundance to long-term warming and fertilization in two arctic ecosystems with contrasting responses of the EM shrub Betula nana. $\bullet$ Ergosterol was used as a biomarker for living fungal biomass in roots and organic soil and ingrowth bags were used to estimate EM mycelial production. We measured 15N and 13C natural abundance to identify the EM-saprotrophic divide in fungal sporocarps and to validate the EM origin of mycelia in the ingrowth bags. $\bullet$ Fungal biomass in soil and EM mycelial production increased with fertilization at both tundra sites, and with warming at one site. This was caused partly by increased dominance of EM plants and partly by stimulation of EM mycelial growth. $\bullet$ We conclude that cycling of carbon and nitrogen through EM fungi will increase when strongly nutrient-limited arctic ecosystems are exposed to a warmer and more nutrient-rich environment. This has potential consequences for below-ground litter quality and quantity, and for accumulation of organic matter in arctic soils.